Gold Futures Price Dynamics Study in the United States - M. Ghazi Algifari; Taufik Chaidir (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Gold is one of the investment instruments that has an important role as a hedge asset in the midst of global economic uncertainty. The development of financial markets and increasing global volatility have made gold futures an increasingly actively traded instrument, especially in the United States market. This study aims to analyze the influence of the US dollar index, the United States stock market index (S&P 500), the Federal Reserve's interest rate, United States inflation, and world crude oil prices on the movement of world gold prices. This study uses monthly time series data for the period January 2010 to December 2025 with a quantitative approach. The analysis method used is the Error Correction Model (ECM) to identify long-term and short-term relationships between variables. The results of the study show that in the long term there is a cointegration relationship between macroeconomic variables and world gold prices. Empirically, the S&P 500 index and world crude oil prices have a significant influence on world gold prices, while the US dollar index, the Fed's interest rate, and US inflation do not show a statistically significant influence. Meanwhile, in the short term, all independent variables do not have a significant effect on world gold prices, but significant and negative Error Correction Term (ECT) values indicate a process of adjustment towards long-term equilibrium. These findings imply that world gold price movements are more influenced by the dynamics of financial markets and the energy sector than by conventional monetary variables, so it is important for investors and market participants to consider these factors in their investment decisions for gold futures.